Therapeutic Anticoagulation in the Presence of a High-Grade Abdominal Solid Organ Injury: A Challenging Case to Manage – Case Report and Literature Review - Yousif Habib Alabboudi; Alaa Haitham Salman; Yousif Hussein El Tayeb; Ali Khammas Yammahi (Dubai Medical Journal)
There are well-established protocols for venous thromboembolism prophylaxis in many patients with a variety of medical and surgical conditions. However, no studies have been published regarding therapeutic anticoagulation in polytrauma patients, who usually present with multiple injuries including vascular injuries and solid organ injuries, which would require therapeutic anticoagulation that increases the risk of bleeding from abdominal solid organ injuries. Here, we present the case of a 45-year-old male, who had a motor vehicle collision and was found to have a grade III splenic injury and had to be started on therapeutic anticoagulation due to popliteal artery injury repair. Our patient was anticoagulated with low-molecular-weight heparin. He had no bleeding complications, and his splenic injury was successfully managed nonoperatively.